2019
DOI: 10.1007/s13201-019-0954-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-criteria-based sub-basin prioritization and its risk assessment of erosion susceptibility in Kansai–Kumari catchment area, India

Abstract: Environmental processes are interrupted by the water action like soil erosion, mass movement as well as siltation on the dam in the undulating catchment area. Soil erosion is one of them and degraded the basin potentiality. This paper demonstrates that erosion susceptibility status in the 13 sub-basins of Kansai-Kumari catchment area has been determined depending upon its morphometric, lithology, geomorphic, land use/land cover (LULC), slope and soil characteristics used by integrated micro-watershed prioritiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Characteristic of climate in this basin, is characterized by southwest tropical monsoon climate, where mean rainfall ranges from 300 mm (drought prone) to 1650 mm (humid or very high rainfall zone). Drainage pattern in this study area is mainly dendritic to sub dendritic nature, where 1st order (5321), 2nd order (1254), 3rd order (298), 4th order (68), 5th order 22 demonstrated that there has significant correlation with drainage, geology, soil, geomorphic landscape and land cover in order to ES (Bhattacharya et al, 2019b). Weaken soil profile, low vegetable cover and prominent rill gullies formation makes high ES in upper basin, whereas dominant laterite tract, steep slope, and agricultural practices creates mild susceptibility in undulating intermediate basin, but dense vegetation, presence of conservation practices resisted ES in the lower basin (Bhattacharya et al, 2020b).…”
Section: Study Areamentioning
confidence: 79%
See 4 more Smart Citations
“…Characteristic of climate in this basin, is characterized by southwest tropical monsoon climate, where mean rainfall ranges from 300 mm (drought prone) to 1650 mm (humid or very high rainfall zone). Drainage pattern in this study area is mainly dendritic to sub dendritic nature, where 1st order (5321), 2nd order (1254), 3rd order (298), 4th order (68), 5th order 22 demonstrated that there has significant correlation with drainage, geology, soil, geomorphic landscape and land cover in order to ES (Bhattacharya et al, 2019b). Weaken soil profile, low vegetable cover and prominent rill gullies formation makes high ES in upper basin, whereas dominant laterite tract, steep slope, and agricultural practices creates mild susceptibility in undulating intermediate basin, but dense vegetation, presence of conservation practices resisted ES in the lower basin (Bhattacharya et al, 2020b).…”
Section: Study Areamentioning
confidence: 79%
“…Morphometric parameters are not considered as only key factors for the determination of ES, but other dominant geo-environmental parameters such as LULC, soil erodibility, slope length-steepness, lithology, geomorphic set-up, etc. are also important (Chauhan et al,2016;Bhattacharya et al, 2019b). In comparison between MCDM methods and SWAT model, effective MCDM methods are helpful to identify the significant role of morphometric parameters on ES; furthermore, linear and aerial aspects are positively correlated with ES (Nooka et al, 2005;Bhattacharya et al, 2019b), but shape aspects are inversely correlated with ES (Patel et al, 2012(Patel et al, , 2013.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations